2005
DOI: 10.1124/jpet.104.082487
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transient Receptor Potential Vanilloid 1 Receptors in Adjuvant-Induced Chronic Arthritis: In Vivo Study Using Gene-Deficient Mice

Abstract: The transient receptor potential vanilloid 1 (TRPV1) receptor is a nonselective cation channel localized on a subset of primary sensory neurons and can be activated by a wide range of stimuli. The present study investigated the role of this receptor in chronic arthritis evoked by complete Freund's adjuvant (CFA) using TRPV1 receptor gene-deleted (TRPV1 Ϫ/Ϫ ) mice and wildtype counterparts (TRPV1 ϩ/ϩ ). In TRPV1 ϩ/ϩ mice, CFA injected intraplantarly into the left hindpaw and the root of the tail induced swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 36 publications
8
126
0
1
Order By: Relevance
“…Abnormal TRPV1 activity can alter the severity and progression of peripheral inflammatory conditions dramatically, including type 1 diabetes (T1D), colitis and arthritis, through mechanisms largely mediated by its local efferent secretory function: too little in T1D, too much in colitis and arthritis (14)(15)(16).…”
Section: Trpv1 Gates Tissue Access and Sustains Pathogenicity In Automentioning
confidence: 99%
“…Abnormal TRPV1 activity can alter the severity and progression of peripheral inflammatory conditions dramatically, including type 1 diabetes (T1D), colitis and arthritis, through mechanisms largely mediated by its local efferent secretory function: too little in T1D, too much in colitis and arthritis (14)(15)(16).…”
Section: Trpv1 Gates Tissue Access and Sustains Pathogenicity In Automentioning
confidence: 99%
“…This includes noxious heat, protons, lipid-derived endovanilloids, and inflammatory mediators (Caterina and Julius, 2001;De Petrocellis and Di Marzo, 2005). Behavioral studies using TRPV1 knock-out mice or selective TRPV1 antagonists have indicated that the receptor is involved in the development of various chronic pain conditions, including those associated with cancer, arthritis, irritable bowel syndrome, and migraine (Caterina et al, 2000;Davis et al, 2000;Akerman et al, 2004;Ghilardi et al, 2005;Jones et al, 2005;Szabo et al, 2005). Accordingly, TRPV1 presents an attractive target for analgesics, and several TRPV1 antagonists are currently under preclinical investigation or clinical trials (Immke and Gavva, 2006;Szallasi et al, 2007).…”
mentioning
confidence: 99%
“…The importance of these receptors in arthritis is highlighted in TRPV1-/-knockout animals that demonstrate elevations in pain threshold and an associated reduction in joint inflammation (46). In addition to enhanced neurotransmitter release, stimulation of TRPV1 is associated with increases in inflammatory mediators contributing to joint inflammation (47).…”
Section: Changes In Trp Stimulationmentioning
confidence: 99%